Parkinson's disease motor subtypes and bilateral GPi deep brain stimulation: One-year outcomes. (June 2020) - Tsuboi, Takashi; Lemos Melo Lobo Jofili Lopes, Janine; Patel, Bhavana; Legacy, Joseph; Moore, Kathryn; Eisinger, Robert S.; Almeida, Leonardo; Foote, Kelly D.; Okun, Michael S.; Ramirez-Zamora, Adolfo
Abstract: Objective: We aimed to explore the differences in motor symptoms and quality of life (QOL) outcomes following bilateral globus pallidus internus deep brain stimulation (GPi DBS), across well-defined motor subtypes of Parkinson's disease (PD), to improve clinical decision making. Methods: This single-center retrospective study investigated bilateral GPi DBS outcomes in 65 PD patients. Outcome measures included the Unified Parkinson's Disease Rating Scale (UPDRS) and Parkinson's Disease Questionnaire (PDQ-39) before and one year after surgery. Outcomes were compared between the tremor-dominant (TD) and postural instability and gait difficulty (PIGD) subtypes and between the TD and akinetic-rigid (AR) subtypes. Results: For the entire cohort, motor function (UPDRS III) in the Off-medication state, motor complications (UPDRS IV), activities of daily living (ADL, UPDRS II), and the ADL and discomfort domains of PDQ-39 significantly improved one year following GPi implantation compared to baseline (effect size = 1.32, 1.15, 0.25, 0.45, and 0.34, respectively). GPi DBS improved the Off-medication UPDRS III scores regardless of the motor subtypes. However, compared to the PIGD and AR patients, the TD patients showed greater improvement in overall UPDRS III postoperatively primarily due to greater tremor improvement in the Off-medication state. The outcomes in akinesia, rigidity, axial symptoms and QOL were similar among all subtypes. Conclusion: Bilateral GPi DBS was effective for advanced PD patients regardless of motor subtypes. Greater tremor improvement in the TD patients accounted for greater Off-medication motor improvement. Longer-term GPi DBS outcomes across different motor subtypes and brain targets should be further studied. Highlights: Bilateral GPi DBS outcomes in 65 PD patients among different motor subtypes. GPi DBS improved the Off-medication UPDRS III regardless of the motor subtypes. TD patients showed greater improvement in UPDRS III than PIGD and AR patients. This difference was largely driven by greater improvement in tremor in TD patients. The outcomes in the other cardinal symptoms and QOL were similar among all subtypes.